Megaphone bureaucracy speaking truth to power in the age of the new normal - Grube, Dennis
Once relegated to the anonymous back rooms of democratic debate, our bureaucratic leaders are increasingly having to govern under the scrutiny of a 24-hour news cycle, hyperpartisan political oversight, and a restless populace that is increasingly distrustful of the people who govern them. Megaphone Bureaucracy reveals how today’s civil servants are finding a voice of their own as they join elected politicians on the public stage and jockey for advantage in the persuasion game of modern governance.